Interannual variability of the Arabian Sea warm pool intensity and its association with monsoon onset over Kerala - SINGH , O. P. (MAUSAM, 2007)
In this paper the relationships between the Arabian Sea warm pool intensity, Southern Oscillation (SO) and the monsoon onset have been discussed. The results show that the peak intensity of the warm pool in the Lakshadweep Sea is significantly correlated with the monsoon onset date over Kerala. Warmer Sea Surface Temperature (SST) anomalies in the warm pool region during April-May are associated with delayed monsoon onset over Kerala though the cause-and-effect relationship is not known. The Southern Oscillation Index (SOI) of March can provide predictive indications of the peak intensity of the warm pool which, normally occurs during April.